Head injury assessment in Italian Rugby Union: a two-seasons prospective analysis - Baioccato, V.; Neunhaeuserer, D.; Gori, N.; Favero, C.; Foccardi, G.; Quinto, G.; Vecchiato, M.; Ieracitano, V. M.; Ermolao, A. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: In Italy, to the best of our knowledge, there is no literature relating to injury and concussion epidemiology in rugby union. Therefore, the primary aim of this study is to describe the incidence of sport-related concussion in Italian rugby union and the associated management of Head Injury Assessment (HIA). METHODS: This is an observational prospective study, analyzing the Italian elite rugby championship (Top 12 and Coppa Italia) for two seasons (2018/2019 and 2019/2020). Twelve male teams of the Italian elite rugby championship were included. The diagnosis of traumatic brain injury was provided by a team doctor with HIA, while no match day doctor or video analysis was available. A concussion expert of Italian Rugby Federation reviewed all the HIAs. The outcome of interest were: incidence, playing situation and mechanism responsible for traumatic brain injury. RESULTS: In the study period, 47 HIAs were performed during matches (45.3/1000 player-match-hours) and 7 concussions were diagnosed by team doctors (6.75/1000 player-match-hours). After the concussion expert HIAs` review, the thirty-three percent of 16 diagnoses were made later, during follow-up, or based on clinical suspicion. Most symptoms complained about by players were neck pain and headache, in 14.6% and 13.4% of HIA, respectively. Concussions were predominately the result of tackling (46.5%) for the tackler (90.9%). CONCLUSIONS: The incidence of concussion in Italian Rugby appears to be low compared to that of rugby outside Italy, which is likely due to the learning curve of HIA and the absence of video analysis and match day doctors during competitions. The implementation of educational projects may be fundamental to promoting HIA process.